2006
DOI: 10.1111/j.1075-122x.2006.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Treatment, and Management of Breast Cancer in Previously Augmented Women

Abstract: Augmentation mammaplasty is rapidly becoming one of the most frequently performed cosmetic surgeries. However, as the augmented patient population ages, major concerns associated with the screening, diagnosis and treatment of breast cancer are being realized. Although current evidence convincingly indicates that breast implants do not play a role in inducing localized or systemic disease, particularly breast cancer, recent studies have shown implants not only reduce the sensitivity of mammography, but interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…In addition to our previous report, 2 publications by Silverstein and colleagues reported that breast implant women presented with more advanced stage at breast cancer diagnosis when compared with nonaugmented women (19,20). Although not statistically significant, several studies showed a tendency toward advanced breast tumors at diagnosis for women who received augmentation mammaplasty (6,(29)(30)(31)(32)(33)(34)(35). However, several other publications found little or no evidence that implant women were diagnosed at a later stage (9,12,(22)(23)(24)(25)(26)(27)(28)57).…”
Section: Principal Findings and Comparison With Previous Studiesmentioning
confidence: 49%
See 1 more Smart Citation
“…In addition to our previous report, 2 publications by Silverstein and colleagues reported that breast implant women presented with more advanced stage at breast cancer diagnosis when compared with nonaugmented women (19,20). Although not statistically significant, several studies showed a tendency toward advanced breast tumors at diagnosis for women who received augmentation mammaplasty (6,(29)(30)(31)(32)(33)(34)(35). However, several other publications found little or no evidence that implant women were diagnosed at a later stage (9,12,(22)(23)(24)(25)(26)(27)(28)57).…”
Section: Principal Findings and Comparison With Previous Studiesmentioning
confidence: 49%
“…Only 3 publications, including our previous report, showed a statistically significant shift toward more advanced breast tumors at diagnosis among augmented women (19)(20)(21). However, several other publications reported no statistically significant differences in breast cancer stage at diagnosis comparing augmented to nonaugmented women (6,9,12,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Furthermore, specific implant characteristics such as implant volume and placement might affect the detection of breast cancer (36).…”
Section: Introductionmentioning
confidence: 72%
“…Irrespectively, the number of breast cancer cases is increasing; in South Korea, there were 16,967 patients with breast cancer in 2011, which was a 4-fold increase compared to the number of patients in 1996. This indicates that the possibility of developing breast cancer is increasing in patients who have undergone breast augmentation [6].…”
Section: Discussionmentioning
confidence: 98%
“…[59][60][61][62] Surveillance of a reconstructed breast is also a collaborative effort on the part of the patient and her surgeon, the medical or radiation oncologist, and the primary physician. The goal of self-examination of the reconstructed breast, like examination of the normal breast, is to detect an area that feels different to the examining fi ngers or looks different in the mirror.…”
Section: Surveillance After Breast Reconstructionmentioning
confidence: 99%